GLASSY MATERIALS AND LIGHT: PART 1 - Nalin, Marcelo [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Manzani, Danilo [UNESP]; Goncalves, Rogeria Rocha; Poirier, Gael; Cassanges, Fabia Castro; Matos, Christiano J. S. de; Mendonca, Cleber R.; Boni, Leonardo de; Misoguti, Lino; Malta, Oscar; Ledemi, Yannick; et al. (Soc Brasileira Quimica, 2016)
2015 is the Year of Light, according to UNESCO. Chemistry has a close relationship with light and one of the materials that allows such synergy is glass. Depending on the chemical composition of the glass, it is possible to achieve technological applications for the whole range of wavelengths extending from the region of the microwave to gamma rays. This diversity of applications opens a large range of research where chemistry, as a central science, overlaps the fields of physics, engineering, medicine, etc., generating a huge amount of knowledge and technological products used for humanity. This review article aimed at discussing some families of glasses, illustrating some applications. Due to the extension of the theme, and all points raised, we thought it would be good to divide the article into two parts. In the first part we focus on the properties of heavy metal oxide glasses, fluoride glasses and chalcogenide glasses. In the second part we emphasize the properties of glassy thin films prepared by sol-gel methodology and some applications, of both glasses as the films in photonics, and more attention was given to the nonlinear properties and uses of photonic fibers.
Keywords: glasses; light; photonics